Lexical-stylistic expression and emotionality of azerbaijani folklore texts (Journal of Oriental Studies, 2019)
Abstract. The aim of our study is to determine the differences between the expressiveness and emotionality of lexical expressions on the material of texts of Azerbaijani folklore. Stylistic vocabulary is the core of the dictionary and is considered a key part of stylistics. Unlike other areas of the language, the dictionary is more advanced and finely fragmented due to the expressive qualities of words and meanings. The creation of this wealth and the study of the possibilities of expressing lexical units is the task facing the lexical style. A stylized dictionary explores the relationship between the true and figurative meanings of vocabulary style functions. Literary criticism and linguistic stylistics investigate the different meanings of a word in context, especially the emotional and expressive linguistic potential of various vocabulary components. In addition to descriptive synchronous lexicology, historical lexicology is also reflected in the style, that is, many authors insist that their etymological roots lead to a more vivid expression when restoring obsolete word meanings. Even the pronunciation of words and phrases is of great importance in the field of vocabulary research. The category of emotions is an emotional expression. The expression in folklore texts comes from various means and acts in various functions. The article discusses the features of synonyms that create expressiveness in a broader sense. Key words: expression, lexics, synonym, word.